Comparing Virtual Reality Telepresence and Traditional Simulation Methods: A Pilot Study - Dang, Bryan K; O'Leary-Kelley, Colleen; Palicte, Jeland S; Badheka, Soham; Vuppalapati, Chandrasekhar (Nursing education perspectives, 2020)
Virtual reality (VR) could enable clinical simulation centers to reach the teaching capacity of traditional hospital practica. This study quantitatively tests VR telepresence against two traditional simulation learning methods using a within-subject design and the Presence Questionnaire. Eight nursing students were randomly assigned and rotated through simulation participation, VR observation, and television observation conditions, completing a questionnaire after each condition. Each condition had a significant effect on presence. Simulation participation yielded the highest perceived presence, followed by VR, and lastly by television observation. This pilot study probed for effect and feedback that will inform a larger experiment.